Tetanus stále aktuální - Chrdle, Aleš; Balejová, Magda (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2020)
Tetanus is a disease caused by tetanotoxin produced in necrotic wounds by Clostridium tetani. It is a very rare disease in Czechia due to successful and effective population-wide vaccination programme, despite the fact that spores of C. tetani are permanently present in the environment. Groups with the highest risk of clinical tetanus include elderly people, immunocompromised individuals, residents of foreign origin with unclear vaccination history, and unvaccinated children. We present four case studies of severe and mild form of tetanus, wound infection with the presence of C. tetani without the development of clinical tetanus in a fully vaccinated individual, and unexpected risk of tetanus in an unvaccinated child. Due to the rare occurrence of tetanus in Czechia, the clinical awareness of the risk of tetanus decreases as well as the clinical experience with diagnosis of early or mild forms of tetanus. Communication skills during the management of contaminated wounds play a critical role in the decision who should get tetanus anatoxin only and who should get antitetanus immunoglobulin along with the active immunization by tetanus anatoxin. Key words: etanus, Clostridium tetani, vaccination, postexposure prophylaxis, vaccine hesitancy, contaminated wounds.
Keywords: Clostridium tetani; tetanus; vakcinace; Child; lidé; Vaccination; senioři; Tetanus; Tetanus Toxoid; dítě; Aged; tetanový toxoid; Humans